17. The Level of Musical Competency Training: A Comparative Study of Full-Time and Distance Students - Nedelcuț Nelida; Pop Ciprian Gabriel; Chiorean Ioana (Review of Artistic Education, 2020)
Estimating the level of competency training at the end of a university programme aims, in the competency-based learning, at a certification of the training’s outcomes. This research wishes to evaluate the degree of specific competency training for a Bachelor programme in music organized by the Gheorghe Dima National Academy of Music from Cluj-Napoca in different forms of learning, namely full-time and distance learning. By means of a questionnaire which measures the appreciation of students on a scale from 1 to 5 we interviewed 60 students who measured their own professional training based on the competencies approved on a national level for music as major subject. We analyzed descriptors characteristic of certain development levels of the key competencies for three specific content areas: the theoretical, methodological, and artistic areas. The main findings of the research, following a comparative analysis of the implementation of programme-specific competencies, reveal superior outcomes in the case of distance students in the development of competencies belonging to the field of performance, the practical activity carried out during the learning process, at their place of work and through participation in artistic productions, thus motivating the students’ interest in acquiring and improving certain specific skills and abilities. The theoretical knowledge and consolidation of the musical language represent the priorities of the full-time students and, by means of a statistical comparison, we highlighted different answers for the results of the questionnaire meant for the assimilation of competencies for each of the descriptors analyzed in this study.